Processos de alcoolização e atenção psicossocial em uma comunidade indígena potiguar - Barreto, Ivan Farias (2022)
The use of alcoholic beverages by Brazilian indigenous peoples is related to a series of historical, psychosocial and health factors that demand urgent measures to minimize related problems. In the state of Rio Grande do Norte (RN), no studies were found on this topic, indicating the existence of a gap in which this work contributes to a better understanding of the issue. The main objective of the thesis is to analyze the processes of alcoholization and the organization of health care services in an indigenous community of RN. Therefore, were carried out three theoretical reviews that analyzed: 1) the construction of public health policies and the organization of psychosocial care services for Brazilian indigenous peoples; 2: alcoholization processes among indigenous peoples in Latin America; 3) the harmful use of alcoholic beverages by indigenous people in Brazil. In addition to these, a field research was undertaken based on semi-structured interviews with indigenous people and health professionals who work in the community. The results of the field research were presented in two chapters which indicate that alcohol intake has been perceived as a naturalized phenomenon and it is associated with several social and health problems. Furthermore, the lack of human resources and the insufficient infrastructure of the care network have hindered the organization of psychosocial care actions in the community, increasing the risks of worsening the mental health of the most vulnerable indigenous people.